CATALYTIC ACTIVITY OF THE COBALT(II) ION WITH PHENYLALANINE COMPLEX IN THE DECOMPOSITION REACTION OF CUMENE HYDROPEROXIDE IN AQUEOUS SOLUTION (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
The formation of Cօ2+ : phenylalanine (Phe) 1:1 complex has been confirmed via kinetic study in aqueous solution at pH>7, which acts as a model catalyst for the decomposition of cumene hydroperoxide (ROOH) in Co2++Phe+ROOH+H2O system. The kinetic expression of a single catalytic decomposition reaction of ROOH under the influence of [CoPhe]+ complex, as well as the Arrhenius equation describing the temperature dependence of the effective constant Keff (=Kcat[Co2+]0[Phe]0) of ROOH decay rate in the temperature range from 323 to 343 K are brought out.
Keywords: cobalt(II) ion; amino acid; phenylalanine; cumene hydroperoxide; complex; catalytic decay; kinetics